Biological thermodynamics - Haynie, Donald T. (Donald Templeton), 1964- (Cambridge University Press, 2001)
Biological thermodynamics provides an introduction to the study of energy transformations for students of the biological sciences. Don Haynie uses an informal writing style to introduce this core subject in a manner which will appeal to biology and biochemistry undergraduate students and be relevant to their studies. The emphasis is on understanding basic concepts and developing problem-solving skills throughout the text, but mathematical complexity is kept to a minimum. Each chapter comprises numerous examples taken from different areas of biochemistry, as well as extensive exercises to aid understanding. Topics covered include energy and its transformation, the First Law of Thermodynamics, the Second Law of Thermodynamics, Gibbs Free Energy, statistical thermodynamics, binding equilibria and reaction kinetics, concluding with a survey of the most exciting areas of biological thermodynamics today, particularly the origin of life on Earth.